Development of hybrid aluminum-air battery fuel-cell system. Issue 1 (1st August 2022) - Tan, Weng Cheong; Saw, Lip Huat; Yew, Ming Chian; Pei-Yu, Kuo; Khor, Zheng Yu; Sun, Dongyang
Abstract: Industrial 4.0 accelerates the need to introduce clean energy to accommodate the increase in electricity demand globally without causing environmental issues. Metal-air battery is a new type of energy storage system in which the metal anode is consumed to generate electricity through the electrochemical reaction. Among various types of the metal anode, aluminum is a promising energy carrier. Aluminum-air battery shows advantages such as high capacity, abundance, low cost, and being environmentally friendly. Traditional aqueous aluminum-air battery experiences restriction from application due to its self-corrosion issues. In this study, instead of reducing or limiting the self-corrosion issues, a different approach is proposed so to make use of the self-corrosion issues of the aluminum-air battery. By incorporating an additional hydrogen-air subcell to the aluminum-air battery, this hybrid system turned the self-corrosion issue into a beneficial reaction by utilizing the hydrogen gas produced from the aluminum anode as the fuel to power the hydrogen-air fuel cell and improving the overall power performance. The electrical performance of each system is studied experimentally using potassium hydroxide electrolytes. The hybrid system shows a great improvement as compared to a single system. The maximum power is improved by more than 40%. This study shows that the hybrid design is feasible in enhancing the aluminum-air battery performance and yet, maintaining low cost and low weight in nature.